ANALISIS KADAR KAFEIN, ANTIOKSIDAN DAN MUTU BUBUK KOPI BEBERAPA INDUSTRI KECIL MENENGAH (IKM) DI KABUPATEN TANAH DATAR [Analysis of Cafein, Antixidant and Quality Levels Coffee Powder of Some Medium Small Industries (IKM) In the Tanah Datar Regency] - Wijayanti, Ruri; Anggia, Malse (Jurnal Teknologi & Industri Hasil Pertanian, 2020)
The caffeine, antioxidant levels, and the quality of coffee powder produced by some small and medium industries in Tanah Datar District were determined in this study. The results of this study are expected to be a reference for the public regarding the caffeine and antioxidants content, as well as the quality of the coffee powder. Samples were obtained from 3 sub-districts in Tanah Datar District, including Salimpauang District, Sungai Tarab District, and Limo Kaum District. The purposive sampling method was used in this study by considering the most famous coffee powder products and well-liked by the public. Analysis of the characteristics of the coffee powder included the caffeine and antioxidant levels, water content, and ash content, as well as organoleptic tests. The results showed that the caffeine content of the coffee powder of most SMI (4 from 6 SMI sample) in the Tanah Datar Regency met the quality standards of SNI.Â  The content of antioxidant was ranged from 32,79 to 39,53%. Likewise, the water (7%)Â  and ash (5%) content have fulfilled the SNI 01-3542-2004 quality standards.Â